Role of Clinical Pharmacist in the Management of Myocardial Infaraction: A Prospective Observational Study (World Journal of Current Medical and Pharmaceutical Research, 2020)
The aim of the present study was to analyze myocardial infarction- Age related risk factors, complications and management.Valuation of age related risk factors in MI patients, identification of frequent type of myocardial infarction, Evaluating the effectiveness of thrombolytic therapy and primary intervention in patients with MI, Assessment of complications of MI and Studying the impact of concomitant diseases on different types of complications. A Prospective observational case series study with 130 cases of patients with myocardial infarction and this study were conducted in department of cardiology in maharaja institute of medical sciences and our work conducted for a period 6 months and we have strictly adhere the Inclusion and exclusion criteria. We concluded that males were more prone to develop MI than females. Incidence of MI was high in age group 51-60 yrs. Cigarette smoking was identified as a major risk factor indicating that life style plays a dominant role than concomitant disorders for early incidence of MI in present generations. Younger population were predisposed to unhealthy life style like smoking, alcohol, fatty diet and we also find out that TLT was effective in treatment of MI. Also, TLT reduced the need for PTCA, and the reason behind subjects required PTCA even after receiving TLT was advanced age. Older subjects were primarily treated with PTCA.